English Club Berbasis Komunitas: Inovasi Literasi Bahasa Inggris Anak di Lingkungan Padat Kota - Ellita Permata Widjayanti; Rahayu Purbasari; Aisah (Jurnal Pemberdayaan Masyarakat, 2026)
Non-formal education-based community service programs play a strategic role in addressing children's literacy challenges in densely populated urban areas. This article describes the implementation and impact of the English Club empowerment program in Buaran, Klender, East Jakarta, initiated by volunteer mothers as an alternative access to English language learning for elementary school children. The program includes the development of English Club learning modules, teacher training, the establishment of a bilingual reading corner, game-based literacy activities, and a parenting seminar in the digital era. Evaluation was conducted through participatory observation, documentation of learning products, and partner reflections. Results indicate that strengthening the capacity of teachers in designing more structured and interactive sessions, increased child engagement in literacy activities and utilization of the reading corner, and positive responses from partners and parents reflecting increased self-confidence and collective awareness of the importance of literacy and family education. These findings confirm that the community-based English Club is effective in improving children's English literacy while empowering women as agents of education in urban environments, in line with SDGs 4 (Quality Education) and 5 (Gender Equality).